Bending the structure: Jacques Lacan along the axis of structuralism and poststructuralism - Günday,Merve; Kaçar,Erman (Felsefe arkivi, 2022)
Lacan wrote and generated ideas at the intersection of structuralism and poststructuralism, and the question of where he stands in this intersection is crucial to understand his conception of the subject. This essay takes the multiplicity of views on Lacan as a structuralist and a poststructuralist as its starting point and aims to weigh these labels against the background of his specific theories and views. We suggest that in his early phase when he was categorised as a structuralist, he had the seeds of his later poststructuralist phase, and when he was generating his poststructuralist ideas, he was building them on his structuralist legacy. This evolution is similar to that of Roland Barthes in that he establishes an ongoing dialog between structuralism and poststructuralism: he is both a threshold figure suggesting an amalgam of these movements, but he is also a dividing figure as his evolution points at the unbridgeable rupture between structuralism and poststructuralism.